MENGULIK PERAN AUDITOR INTERNAL DALAM MELAKUKAN DETEKSI DAN PENCEGAHAN FRAUD DI PERGURUAN TINGGI - Gita Arasy Harwida (InFestasi, 2015)
This research was examining and digging the role SPI in two universities (state university and private university)in East Java Province in detecting and preventing fraud. Also, we would like to discover the possibility of role conflict for SPI member who plays two roles as an auditor as well as a lecturer. Another objective of this research is to propose a model of synergy between the SPI of the state university and the private university in order to play a meaningful role in detecting and preventing fraud in the higher education institution and to achieve the Good University Governance (GUG).The result shows that there are differences role play between SPI in the state university and the private university. The SPI in the private university has more powerful role because the hierarchy is also implemented consistently in the battle field, and also none of its SPI member plays double roles like SPI member in the state university. The fact also indicates that both SPI have strong commitment to detect as well as prevent the fraud in their institutions. However, the existence of SPI role is also be effected by the commitment of its Rector/Director in order to utilize SPI to achieve GUG.